Eve in Overalls - women war workers pamphlet, c. 1944 (page 2) (1944)
1944 "Eve in Overalls - women war workers pamphlet, c. 1944 (page 2)" [T0174b.jpg], 1944 This pamphlet by the Belgian socialist politician, Arthur Wauters, although not attributed to any government department uses official photographs to illustrate the valued work undertaken by women during the Second World War.